Transgenerational technology and interactions for the 21st century : perspectives and narratives - Marston, Hannah R.; Shore, Linda; Stoops, Laura; Turner, Robbie S. (Emerald Publishing Limited, 2022)
Transgenerational Technology and Interactions for the 21st Century explores how we as humans navigate the 21st Century, interacting with technologies, including those that are intended to support and enhance our experiences across the lifespan. This manifesto, composed with humanity at the front and centre, pinpoints succinctly the critical considerations of people, technology and inequalities intersecting across our 21st century ecosystems. With a special focus on bridging interdisciplinary research, creative and co-production approaches, the authors explore and present cutting edge discourse, building on previous research to form contemporary and inform future awareness and strategies to societal experiences. The authors argue that it is time to re-evaluate how we move forward in a multi-faceted society, with the ever growing reliance of technology but yet many voices are not heard, left behind or not even considered. This creative and collaborative response is suited to researchers, academics, designers, industry and stakeholder professionals who have an interest the fields of technology, design, sociology and innovation.